Rasio Hip-Acromion Sebagai Faktor Tingkat Kebugaran - Wayan Rusni; Tanjung Subrata; Trisna Sumadewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
"Baswara Medical Assistance Team (TBM)" is an organizational forum that facilitates students in student activities, especially for handling emergencies and humanity in the field. TBM members are required to have excellent physical fitness to be able to provide basic medical assistance. While attending medical education, it turns out that the fitness level of students continues to experience a decline, which is more evident when they are in the pre-clinical education period. The purpose of this study was to determine the relationship between the hip-acromion ratio and the fitness level of TBM FKIK students. The design used was cross-sectional for 7 months, involving 68 students from TBM FKIK Unwar who were selected by simple random sampling technique. Measuring tools in the form of observation sheets, tension meter, scales and height meter. The data were analyzed descriptively and then tested the hypothesis using the Spearman rank test. The results showed a p value of less than 0.05 for the correlation between the hip-acromion ratio and sit ups and cardio-pulmonary endurance.Keywords: hip-acromion ratio; fitness; sit ups; push ups; cardiorespiratory endurance ABSTRAK “Tim Bantuan Medis Baswara (TBM)” adalah wadah organisasi yang memfasilitasi mahasiswa dalam kegiatan kemahasiswaan, terutama untuk penanganan kegawatdaruratan dan kemanusiaan di lapangan. Anggota TBM dituntut memiliki kebugaran fisik yang prima untuk dapat memberikan pertolongan medis dasar. Selama mengikuti pendidikan kedokteran, tingkat kebugaran mahasiswa ternyata terus mengalami penurunan, yang tampak lebih nyata ketika mereka dalam masa pendidikan pre-klinik. Tujuan penelitian ini adalah untuk mengetahui hubungan antara rasio hip-acromion dengan tingkat kebugaran mahasiswa TBM FKIK. Rancangan yang digunakan adalah cross-sectional selama 7 bulan, yang melibatkan 68 mahasiswa anggota TBM FKIK Unwar yang dipilih dengan teknik simple random sampling. Alat ukur berupa lembar observasi, tensi meter, timbangan dan meteran tinggi badan. Data dianalisis secara deskriptif lalu dilakukan pengujian hipotesis menggunakan uji Spearman rank. Hasil penelitian menunjukkan nilai p kurang dari 0,05 untuk korelasi antara rasio hip-acromion dengan sit up dan daya tahan jantung-paru.Kata kunci: rasio hip-acromion; kebugaran; sit up; push up; daya tahan jantung-paru